The Relationship of Knowledge and Attitude with Utilization of Baharu River Water in Kelambir Village, Hamparan Perak District, Deli Serdang Regency - Rosdiana Rosdiana; M. Habibi Yusup (Journal La Medihealtico, 2022)
Water is an important factor in meeting the vital needs of living things such as drinking water or other household needs. The water used must be free from germs and do not contain toxic materials. This study was to determine the relationship between knowledge and attitudes with the use of Baharu River water in Kelambir Village, Hamparan Perak District, Deli Serdang Regency. This research is an analytic survey with a cross sectional design. The population of this study was the entire community in Kelambir Village, namely 267 respondents, the sample in this study was 73 respondents. Data analysis used univariate and bivariate analysis with chi-square test. The chi-square test shows the probability value of each variable, including knowledge p = 0.008, and attitude p = 0.008. This research is that there is a relationship between knowledge and attitudes with the use of Baharu River water in Kelambir Village, Hamparan Perak District, Deli Serdang Regency. It is hoped that the people in the Baharu River flow will know and get sources of information about the utilization of river water and how to use it properly and correctly and the community is able to maintain the watershed so that it is not polluted and the community can use river water properly in Kelambir Village, Hamparan Perak District. Deli Serdang Regency.